Dissociation of quantifiers and object nouns in speech in focal neurodegenerative disease. (August 2016) - Ash, Sharon; Ternes, Kylie; Bisbing, Teagan; Min, Nam Eun; Moran, Eileen; York, Collin; McMillan, Corey T.; Irwin, David J.; Grossman, Murray
Abstract: Quantifiers such as many and some are thought to depend in part on the conceptual representation of number knowledge, while object nouns such as cookie and boy appear to depend in part on visual feature knowledge associated with object concepts. Further, number knowledge is associated with a frontal-parietal network while object knowledge is related in part to anterior and ventral portions of the temporal lobe. We examined the cognitive and anatomic basis for the spontaneous speech production of quantifiers and object nouns in non-aphasic patients with focal neurodegenerative disease associated with corticobasal syndrome (CBS, n=33), behavioral variant frontotemporal degeneration (bvFTD, n=54), and semantic variant primary progressive aphasia (svPPA, n=19). We recorded a semi-structured speech sample elicited from patients and healthy seniors (n=27) during description of the Cookie Theft scene. We observed a dissociation: CBS and bvFTD were significantly impaired in the production of quantifiers but not object nouns, while svPPA were significantly impaired in the production of object nouns but not quantifiers. MRI analysis revealed that quantifier production deficits in CBS and bvFTD were associated with disease in a frontal-parietal network important for number knowledge, while impaired production of object nouns in all patient groups was related to disease in inferior temporal regions important for representations of visual feature knowledge of objects. These findings imply that partially dissociable representations in semantic memory may underlie different segments of the lexicon. Highlights: Corticobasal syndrome (CBS) and behavioral variant FTD (bvFTD) are not aphasic. CBS and bvFTD have calculation deficits. We find that CBS and bvFTD produce fewer quantifiers in their speech. Reduced quantifier production is related to frontal-parietal disease. Object noun deficits are related to left temporal disease in CBS, bvFTD and svPPA.